Storm impacts along European coastlines. Part 1: The joint effort of the MICORE and ConHaz Projects - Ciavola, Paolo (2018)
The current paper discusses the topic of marine storm impact along European coastlines, presenting results from two FP7 Projects currently focusing on this topic, one working on the physical aspects of the problem (MICORE) and the other one on the socio-economic implications (ConHaz). The MICORE Project aims to provide on-line predictions of storm-related physical hazards (hydrodynamic as well as morphodynamic). The ConHaz Project addresses the socio-economic implications should these (or other) hazards actually materialize. Together these projects aim to deliver crucial information for emergency response efforts, while realizing the practical limitations for information processing and dissemination during crisis situations. The MICORE Project has developed and demonstrated on-line tools for reliable predictions of the morphological impact of marine storm events in support of civil protection mitigation strategies. The project specifically targeted the development of early warning and information systems to support short term emergency response in case of an extreme storm event. The current paper discusses in detail the outcome of an activity of databasing historical storm data. No clear changes in storminess were observed, except for some storm proxies (e.g. surges) and only at some locations (e.g. northern Adriatic, southern Baltic, etc.). The ConHaz Project undertook a desktop study of the methods normally used for evaluating the impact of marine storms and the associated coastal hazards considering direct costs, costs due to disruption of production processes, indirect costs, intangible costs, and costs of adaptation and mitigation measures. Several methods for cost estimation were reviewed. From the review it emerged that normally end-users only evaluate direct costs after the storms, while the cost of adaptation and mitigation measures is only done strategically in the context of Integrated Coastal Zone Management plans. As there is no standardized method for cost evaluations in this field, it is suggested that clear guidelines should be produced on the basis of simplicity for use by end-users. The integration between historical databases of the physical parameters of storms and detailed cost evaluation information would support the development of a knowledge background in end-users and justify the development of adaptation strategies.